2015
DOI: 10.1177/0020764014565797
|View full text |Cite
|
Sign up to set email alerts
|

Ways of coping of Chinese caregivers for family members with schizophrenia in two metropolitan cities: Guangzhou and Hong Kong, China

Abstract: There were significant differences in the coping strategies of family caregivers for people with schizophrenia in the two Chinese cities. Further studies are warranted to investigate factors affecting their coping strategies and their effects on psychological health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
3
11
0
1
Order By: Relevance
“…Thus, more unbalanced flexibility levels were associated with greater feelings of burden among caregivers, which are related to higher levels of psychological distress [6] 2016. Caregivers of schizophrenic patients use the effective and ineffective coping methods of crying, denial, anger, withdrawal from social life, aggressive behaviors, positive thinking, knowledge acquisition, receiving support from friends and neighbors, and seeking social support together [10][11][12][13][14]. However, it has been reported that the coping strategies of caregivers are insufficient and caregivers are in need of nursing interventions to improve their coping [11].…”
Section: Flexible Line Of Defensementioning
confidence: 99%
“…Thus, more unbalanced flexibility levels were associated with greater feelings of burden among caregivers, which are related to higher levels of psychological distress [6] 2016. Caregivers of schizophrenic patients use the effective and ineffective coping methods of crying, denial, anger, withdrawal from social life, aggressive behaviors, positive thinking, knowledge acquisition, receiving support from friends and neighbors, and seeking social support together [10][11][12][13][14]. However, it has been reported that the coping strategies of caregivers are insufficient and caregivers are in need of nursing interventions to improve their coping [11].…”
Section: Flexible Line Of Defensementioning
confidence: 99%
“…In Chinese societies, which are bound by extensive kinship obligations, family members often take an active role in caregiving (Lam et al, 2013), whether living with or apart from a family member with mental illness. Many have experienced a burden, and found that caregiving has had adverse effects on their physical and mental health and quality of life (Lam et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a Chinese city like Hong Kong, family caregivers are affected by the illness of their family members, contextual problems and the current inadequacies of the mental health care system (Pearson and Lam, 2002). They are under stress and are psychologically at risk (Lam et al, 2015). Many family caregivers in Mainland China have also been found to have poor mental health and to be bearing a heavy burden of care (Li et al, 2007; Liu et al, 2007; Yao, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have noted that EE was formed with English cultural norms in mind, valuing the independence of the person with psychosis (Singh, 2013). In contrast, Chinese culture has traditionally placed emphasis on interdependence (Lam et al, 2015). Chinese parenting practices can be seen to be guided by the notion of 'guan', which indicates a willingness for parents to direct their child through control and regulated teaching.…”
mentioning
confidence: 99%